ACTB Variants Confer the Genetic Susceptibility to Diabetic Kidney Disease in a Han Chinese Population - Li, Mengxia; Wu, Ming; Qin, Yu; Zhou, Jinyi; Su, Jian; Pan, Enchun; Zhang, Qin; Zhang, Ning; Sheng, Hongyan; Dong, Jiayi; Tong, Ye; Shen, Chong (Frontiers in Genetics, 2019)
Beta-actin (ACTB) loss-of-function mutations result in a pleiotropic developmental disorder of kidney. The present study aims to explore whether the common variants at the ACTB gene contribute to diabetic kidney disease (DKD) susceptibility in patients with type 2 diabetes mellitus (T2DM). From the baseline population of 20,340 diabetic patients, 1,510 DKD cases and 1,510 age-matched T2DM controls were selected. All subjects were Han Chinese. Three tagging single nucleotide polymorphisms (SNPs), rs852423, rs852426 and rs2966449 at the ACTB gene were genotyped. Logistic regression was performed to estimate the association with DKD. SNPs rs852426 and rs2966449 were significantly associated with DKD (Additive model, OR=1.217 and 1.151, P=0.001 and 0.018, respectively). The association of rs852426 with DKD was still remained statistically significant after Bonferroni correction and particularly significant in the population >70 years old rather than ≤70 years old (P=0.032 for heterogeneity test). Furthermore, the association of rs852426 with DKD was observed in populations of male and females without smoking, drinking and with duration for T2DM over 10 years. The association of rs2966449 with DKD was also found in the populations of >70 years old, male, without smoking, without drinking and with duration for T2DM over 10 years. The estimated glomerular filtration rate (eGFR) levels of the individuals with TT and CC genotypes of rs2966449 were significantly lower than that of TC genotype in DKD cases (P=0.021). The present study provides evidence that the ACTB variants i.e. rs852426 and rs2966449 may confer the genetic susceptibility to DKD in a Han Chinese population.